1994
DOI: 10.12693/aphyspola.86.853
|View full text |Cite
|
Sign up to set email alerts
|

Signal Photoelectron Yield Dependence on the X-Ray Angle of Incidence

Abstract: The photoelectron emission from solids irradiated by X-rays was described by the analytical theory of electron transport and simulated by the Monte Carlo technique. The medium energy electron transport problem is treated by means of a Boltzmann type kinetic equation satisfying appropriate boundary conditions. The solution of the transport equation was obtained in the transport approximation based on the generalized radiative field similarity principle. Simple and reliable formalism was derived for both the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…As seen in literature 29 and discussed earlier, the surface Mn valence is smaller than þ3.3. Another exponential term is added to Equation (1) to better represent the depth dependent Mn valence…”
supporting
confidence: 58%
See 2 more Smart Citations
“…As seen in literature 29 and discussed earlier, the surface Mn valence is smaller than þ3.3. Another exponential term is added to Equation (1) to better represent the depth dependent Mn valence…”
supporting
confidence: 58%
“…¼ 1.0 nm, consistent with the electron mean free path in LSMO. 29 The best fit gave surface, interface, and bulk valences of V surf % 2.0, V int % 2.52, and V bulk % 3.36. The best fit curves are shown in short dashed pink in Figs.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…4,[17][18][19][20][21][22] It was found that the transport approximation predictions for different emission characteristics were astonishingly accurate, even in the intermediate case of scattering parameters, i ϳ tr , which is of the most relevance for XPS. The discrepancies between the Monte Carlo and analytical results, as a rule, do not exceed several percent as regards the angular and energy spectrum of emitted electrons, 19,20 the emission depth and the traveled pathlength distributions, 17,21 the mean escape depth, 4 the total photoelectron yield, 22 and so on. In view of this it seems appropriate to apply the transport approximation to the problem of signal photoelectron emission by polarized x rays.…”
Section: Solution Of Transport Problemmentioning
confidence: 99%